The Susan B. Anthony you never knew - Collier, James Lincoln, 1928- (Children's Press, 2004)
Examines the life of American feminist Susan B. Anthony, discussing her childhood and family, her friendship with fellow crusader Elizabeth Cady Stanton, and her role in the campaign for women's rights.